The myth of dual class shares: lessons from Asia's financial centres - Yan, Min (The journal of corporate law studies, 2021)
The recent revival of dual class shares in the US and reforms in the leading financial centres in Asia to accommodate listings with such share structures, has brought the spotlight back to them. While there are contradictory standpoints regarding the implication of separating insiders' control from their cash flow rights, the ongoing debate over the viability of dual class shares has largely been shifted to how to restrain the associated governance risks. Measures such as sunset provisions and limitation of voting differentials are designed to restrain the control stemming from multiple voting shares and provide mandatory safeguards to holders of inferior voting shares. However, these safeguarding measures may compromise the value of differentiated voting arrangements. The extremely low percentage of new IPOs with dual class shares in Asia's leading financial centres at least partly reflects the reduced attraction of such share structures when mandatory safeguards are stringent. Thus, this article argues that safeguarding measures are a double-edged sword, which not only help mitigate increased governance risks but also undermine the insulation of controllers from external investor and market influence; it calls for a more cautious use of such ex ante mechanisms in order that the initial purpose of permitting listings with dual class shares is not compromised.